Inokulasi Rhizobium dan Populasi Tanaman terhadap Pertumbuhan dan Hasil Kedelai pada Sistem Tanpa Olah Tanah - Aldhera Nanda Augusta; Supriyono Supriyono; Sri Nyoto (Agrotechnology Research Journal, 2019)
One of the factors of less soybean productivity of in Indonesia is caused by the N fixation. It can decrease the growth and the yield of soybean. One of the methods to overcome the N fixation is by rhizobium inoculation. The aim of this research was to observe the effects of rhizobium inoculation dosage and the number of seed per hole (population) to the growth and yield of soybean. The method used was Split Plot Randomized Completely Block Design (RCBD). The treatments were type of inoculant rhizobium dosage: without treatment, 3 and 6 g kg-1 as well as the number of plants, 2 and 3 on planting pit. The result showed that the lowest plant height was in soybean without inoculated by rhizobium and 3 plants per planting pit. The lowest branches number was three plants per planting pit when compared than 2 plants on planting pit. Rhizobium inoculation was not significant to affect the number of leaves, number of branches, leaf area index, number of beans per pod, number of pods per plant, weight of 100 seeds, fresh weight, dry weight and yield.